Path coefficient studies in gladiolus for horticultural traits under Bihar conditions - Priyanka Kumari; Deepti Singh (Annals of Agricultural Research, 2024)
The present investigation was carried out at the Department of Horticulture (Veg. and Flori.), BAU, Sabour to evaluate thirteen genotypes of gladiolus under Bihar conditions in Randomized Block Design (RBD) with three replications. The experimental findings revealed that there were significant differences among all genotypes for various growth, floral and corm attributes. Based on path coefficient analysis, average fresh weight of spike (1.119, 0.998), spike yield per plot (1.021, 0.996), spike vase life (0.043, 0.031), number of florets per spike (0.002, 0.023) and rachis length (0.002, 0.009) had direct positive effect towards number of spikes per plant at both genotypic and phenotypic level, respectively except at genotypic level plant height (0.041) had direct positive effect and at phenotypic level spike length (-0.117) had direct negative effect towards number of spikes per plant.